(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the methods of analysis of iodine in natural objects. In the world, iodine is used in the food and pharmaceutical industries, medicine and veterinary medicine, in the production of mineral fertilizers, is used in the chemical industry as a catalyst, in the production of some highly pure materials, special glass and synthetic rubbers. In addition, iodine is a major factor in preventing endemic goiter and other types of diseases. Therefore, in order to meet the demand for iodine in the republic, the priority task is to develop a perfect technology for obtaining iodine on an industrial scale from the main sources, such as underground hydrothermal waters.